Screening for abnormal heart sounds and murmurs by implementing neural networks - Visagie, Claude (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2007.